# PART 3.

4: DIFFERENTIAL EQUATIONS

X.1 FIRST ORDER, FIRST DEGREE, DIFFERENTIAL EQUATIONS:

Separable:
∫ ∫
=
=
=
dx x f dy y g
dx x f dy y g
y g
x f
dx
dy
) ( ) (
) ( ) (
) (
) (

Linear/Integrating Factor:
( )

× =

=
= × +
dx x Q x I
x I
y
e x I
x Q y x P
dx
dy
dx x P
) ( ) (
) (
1
) (
) ( ) (
) (

Homogeneous:

|
¹
|

\
|
= =
=
x
y
F y x f
dx
dy
y x f y x f
) , (
) , ( ) , ( λ λ

Let
dx
dv
x v
dx
dy
x
y
x v + = ∴ = , ) (
∫ ∫
=

=

− =
= + ∴
x
dx
v v F
dv
x
dx
v v F
dv
v v F
dx
dv
x
v F
dx
dv
x v
) (
) (
) (
) (

Exact:
0 ) , ( ) , ( ) , ( = + → = dy y x N dx y x M y x f
dx
dy

If:
x y
N M =
When: N F M F
Y X
= = &
Therefore,
( )
... ) (
) ( ' ) (
) ( ) , ( ) , (
= ∴
= + Φ = + Φ

=
+ Φ = =

y g
N y g y g
y
F
y g y x dx y x M F
Y Y
So: ( ) C y g y x y x F = + Φ = ) ( ) , ( ,

Bernoulli Form:
( ) ( )
n
y x Q y x P
dx
dy
= +
Let:
( )
( ) ( )
( ) ( )
( ) ( ) ( ) ( ) x Q n v x P n
dx
dv
x Q y x P
dx
dv
n
y x Q y x P
dx
dv
n
y
dx
dv
n
y
dx
dy
dx
dy
y n
dx
dv
y v
n
n
n
n
n
n
− = − + ⇒
= +

= +

= ∴
− = ∴
=

1 1
1
1
1
1
1
1
1

This is a linear 1
st
ODE

( )
( )
( )
( )
( ) ( )
( ) ( )
( ) ( ) ( ) n
dx x P n
dx x P n
n
n
dx x P
dx x Q n e
e
dx x Q x I
x I
v y
dx x Q x I
x I
v
e x I
x Q v x P
dx
dv

|
¹
|

\
|
− ×

= × = =
× =

=
= × +
∫ ∫

1
1
1
1
2
1
2
) (
2 2
1
1
) ( ) (
) (
1
) ( ) (
) (
1
) (
) ( ) (
2

X.2 SECOND ORDER, FIRST DEGREE, DIFFERENTIAL EQUATIONS:

Where
) ( ' ' '
) (
2
2
x f cy by ay
x f cy
dx
dy
b
dx
y d
a
= + +
= + +

Greg’s Lemma:

( ) ( ) ( ) ( )
( )( )
( ) ( )
( ) ( )
x x n n
x x
x x
x x
e n e x D
e e x D
e xe D
e x p e x p D
α α
α α
α α
α α
α
α
α
α
!
2
'
2 2
= −
= −
= −
= −

Homogeneous:

0
0 ' ' '
2
= + + ⇒
= + +
c bm am
cy by ay

a
ac b b
m
2
4
2
− ± −
=
There are three possible outcomes:
1)
2 1
, m m where
2 1
m m ≠
x m x m
h
Be Ae y
2 1
+ = ⇒ { }
x m x m
e e S
2 1
, =
2)
2 1
, m m where
2 1
m m = ( )
x m
h
e Bx A y
1
+ = ⇒
{ }
x m x m
xe e S
1 1
, =
3) j m β α ± =
2 , 1
( ) ( ) ( ) x B x A e y
x
h
β β
α
sin cos + = ⇒
( ) ( ) { } x e x e S
x x
β β
α α
sin , cos =

Undetermined Coefficients
) ( ' ' ' x f cy by ay = + + , where ) (x f is in the form of

1) A polynomial
2) ( ) kx sin α
3)
kt
e α

NB: Multiplication is OK: eg:
x
e x x f
3
3 ) ( =

Step 1: Solve for the homogeneous case 0 ' ' ' = + + cy by ay

{ }
2 1
2 2 1 1
, y y S
y c y c y
h
=
+ = ∴

Step 2: Determine the spanning set

1) A polynomial
0 1
1
1
A x A x A x A y
n
n
n
n p
+ + + = ⇒

{ } ,... ,
1 −
=
n n
x x T
2) ( ) kx sin α ) cos( ) sin( kx B kx A y
p
+ = ⇒ ( ) ( ) { } kx kx T sin , cos =
3)
kt
e α
kt
p
Ae y = ⇒ { }
kt
e T =

NB: Multiplication is OK: eg:
( )( )
( )( ) E Dx Cx Bx e y
E Dx Cx Bx Ae y
e x x f
x
p
x
p
x
+ + + =
+ + + =
=
2 3
2 3
3
3 ) (

Step 3: Determine the form of y
p
with arbitary coefficients

Case 1: When Φ = ∩T S
Then y
p
is a linear combination of the elements of T

Case 2: When Φ ≠ ∩T S (ie: y
p
is part of y
h
)
Multiply each element in T by x to get a new set T’ and then recheck if
Φ = ∩ ' T S . This is now a case 1, otherwise repeat the process until Φ = ∩ ' T S

Step 4: Determine the coefficients of y
p
by substituting
p p p
y y y ' ' , ' , back into the orginal
differential equation and comparing the coefficients with ) (x f

Then,
...
3 2 1
+ + + + =
p p p h
y y y y y

If the intital values are given, go on to solve for the constants within the homogeneous part.

Variation of Parameters
Where
) ( ' ' '
) (
2
2
x f cy by y
x f cy
dx
dy
b
dx
y d
= + +
= + +
and the method of undetermined coefficients is not
suitable.

Step 1: Solve for the homogeneous case 0 ' ' ' = + + cy by ay

2 2 1 1
u c u c y
h
+ = ∴

Step 2: Assume that there is a solution of the differential equation of the form:
2 2 1 1 2 2 1 1
) ( ) ( ) ( ) ( u v u v x u x v x u x v y + = + =
Such that 0 ' ' ) ( ) ( ' ) ( ) ( '
2 2 1 1 2 2 1 1
= + = + u v u v x u x v x u x v
Therefore,

' ' ' ' ' ' ' ' ' '
' ' ' ' ' ' '
2 2 2 2 1 1 1 1
2 2 1 1 2 2 2 2 1 1 1 1
2 2 1 1
u v u v u v u v y
u v u v u v u v u v u v y
u v u v y
+ + + =
+ = + + + =
+ =

Substituting into the differential equation:

( ) ( ) ( )
( ) ( )
' ' ' ' ) (
' ' ' ' ' ' ' ' ' ' ) (
' ' ' ' ' ' ' ' ' ' ) (
' ' ' ' ' ' ' ' ' ' ) (
2 2 1 1
2 2 1 1 2 2 2 2 1 1 1 1
2 2 1 1 2 2 2 2 2 2 1 1 1 1 1 1
2 2 1 1 2 2 1 1 2 2 2 2 1 1 1 1
v u v u x f
v u v u v cu bu u v cu bu u x f
v u v u v cu v bu v u v cu v bu v u x f
u v u v c u v u v b u v u v u v u v x f
+ =
+ + + + + + + =
+ + + + + + + =
+ + + + + + + =

As 0 ' ' ' & 0 ' ' '
2 2 2 1 1 1
= + + = + + cu bu u cu bu u
We know that 0 ' '
2 2 1 1
= + v u v u and ) ( ' ' ' '
2 2 1 1
x f v u v u = +
Step 3:
Solving the equations above by Cramer’s Rule.

( )
(
¸
(

¸

=
(
¸
(

¸

(
¸
(

¸

x f v
v
u u
u u 0
'
'
' '
2
1
2 1
2 1

( )
( )
( )
( )
( )
( )
2 1
1
2 1
2 1
1
1
2
2 1
2
2 1
2 1
2
2
1
,
' '
'
0
'
,
' '
'
0
'
u u W
u x f
u u
u u
x f u
u
v
u u W
u x f
u u
u u
u x f
u
v
=
(
¸
(

¸

(
¸
(

¸

=

=
(
¸
(

¸

(
¸
(

¸

=

Step 4:

( )
( )
( )
( )
( )
( )
( )
( )
∫ ∫ ∫
∫ ∫ ∫
=
(
¸
(

¸

(
¸
(

¸

= =

=
(
¸
(

¸

(
¸
(

¸

= =
dx
u u W
u x f
dx
u u
u u
x f u
u
dx v x v
dx
u u W
u x f
dx
u u
u u
u x f
u
dx v x v
2 1
1
2 1
2 1
1
1
2 2
2 1
2
2 1
2 1
2
2
1 1
,
' '
'
0
'
,
' '
'
0
'

p h
p
h
y y y
x u x v x u x v y
x u c x u c y
+ =
+ =
+ =
) ( ) ( ) ( ) (
) ( ) (
2 2 1 1
2 2 1 1

Euler Type
Of the form: 0 , 0 ' ' '
2
> = + + x cy bxy y ax
Characteristic Equation: ( )( ) ( ) 0 1 = + + − c r b r r a or
( )
0
1
2
= +

+ y
a
c
r
a
b
r
There are three possible outcomes:
1)
2 1
, r r where
2 1
r r ≠ 0 ,
2 1
2 1
> + = ⇒ x x C x C y
r r
h

2)
2 1
, r r where
2 1
r r = ( ) 0 , ln
1 1
2 1
> + = ⇒ x x x C x C y
r r
h

3) j r β α ± =
2 , 1
( ) ( ) ( ) ( ) ( ) 0 , ln sin ln cos > + = ⇒ x x B x A x y
h
β β
α

Reduction of Order
Of the form: 0 ) ( ' ) ( ' ' ) (
3 2 1
= + + y x f y x f y x f where a solution is known
) (
1
x g y =
Therefore, let
) ( ' ' ) ( ) ( ' ) ( ' 2 ) ( ) ( ' ' ' '
) ( ' ' ) ( ) ( ' ) ( ' ) ( ' ) ( ' ) ( ) ( ' ' ' '
) ( ' ) ( ) ( ) ( ' '
) ( ) (
x g x v x g x v x g x v y
x g x v x g x v x g x v x g x v y
x g x v x g x v y
x g x v y
+ + = ∴
+ + + = ∴
+ = ∴
=

Substituting Yields:

( ) ( ) ( ) 0 ) ( ) ( ) ( ) ( ' ) ( ) ( ) ( ' ) ( ) ( ' ' ) ( ) ( ' ) ( ' 2 ) ( ) ( ' ' ) (
3 2 1
= + + + + + x g x v x f x g x v x g x v x f x g x v x g x v x g x v x f
This should cancel down to only include ' ' '&v v
( ) ( ) 0 ) ( ) ( ' ) ( ) ( ' ) ( ' 2 ) ( ) ( ' ' ) (
2 1
= + + x g x v x f x g x v x g x v x f
Therefore, let ' ' ' '& v u v u = =
( ) ( )
( ) ( )
( )
( )
( )
( )
( )
( )
( )
( )
( )
( )
( )
( )
( )
( )
( )
) (
) (
) ( '
) (
) ( ) (
) ( ) ( ) ( ' ) ( 2
) ( ln
) ( ) (
) ( ) ( ) ( ' ) ( 2
) (
) ( '
) ( ) (
) ( ) ( ) ( ' ) ( 2
) (
) ( '
0 ) ( ) ( ) ( ' ) ( 2 ) ( ) ( ) ( ) ( '
0 ) ( ) ( ) ( ) ( ' ) ( ) ( 2 ) ( ) ( ' ) (
0 ) ( ) ( ) ( ) ( ' ) ( 2 ) ( ) ( ' ) (
) ( ) (
) ( ) ( ) ( ' ) ( 2
) ( ) (
) ( ) ( ) ( ' ) ( 2
) ( ) (
) ( ) ( ) ( ' ) ( 2
) ( ) (
) ( ) ( ) ( ' ) ( 2
1
2 1
1
2 1
1
2 1
2 1 1
2 1 1
2 1
1
2 1
1
2 1
1
2 1
1
2 1
x g dx e y
dx e x v
e x v
e x u
dx
x g x f
x g x f x g x f
x u
dx
x g x f
x g x f x g x f
du
x u
x u
x g x f
x g x f x g x f
x u
x u
x g x f x g x f x u x g x f x u
x g x u x f x g x u x f x g x u x f
x g x u x f x g x u x g x u x f
dx
x g x f
x g x f x g x f
dx
x g x f
x g x f x g x f
dx
x g x f
x g x f x g x f
dx
x g x f
x g x f x g x f
× =
=
=
=
+ −
=
+ −
=
+ −
=
= + +
= + +
= + +

∫ ∫

+ −

+ −

+ −

+ −

General solution is of the form:
2 2 1 1
y c y c y + =
Note: Constants can be combined into a single constant to simplify working if required.

Power Series Solutions:
Where
( ) ( ) ( )
( ) ( ) ( ) 0 ' ' '
0
2
2
= + +
= + +
y x R y x Q y x P
y x R
dx
dy
x Q
dx
y d
x P
0
x

Case 1: About an Ordinary Point
Where ( ) 0
0
≠ x P and analytic at
0
x
Assume
( ) ( ) ( ) ( )
∑ ∑ ∑

=

=

=
− − = − = − =
2
2
0
1
1
0
0
0
1 ' ' , ' ,
n
n
n
n
n
n
n
n
n
x x a n n y x x na y x x a y
Note:
( ) ( )
( ) ( ) ( ) ( ) ( ) ( )
∑ ∑ ∑
∑ ∑

=

=

=

=

=

− − = − − = − − =
− = − =
0
2
0
1
2
0
2
2
0
0
1
0
1
1
0
1 1 1 ' '
'
n
n
n
n
n
n
n
n
n
n
n
n
n
n
n
x x a n n x x a n n x x a n n y
x x na x x na y

• Substitute into the differential equation.
• Adjust the indices in terms of
n
x
• Obtain a recurrence relation of
n
a in terms of
1 0
&a a
• Express
n
a in terms of
1 0
&a a
( )
2 1 1 0
0
0
y a y a x x a y
n
n
n
+ = − =

=

Case 2: About a Regular Singular Point
Where ( ) 0
0
= x P , ( )
( )
( )
|
|
¹
|

\
|

x P
x Q
x x
x x
0
0
lim exists and ( )
( )
( )
|
|
¹
|

\
|

x P
x R
x x
x x
2
0
0
lim exists.
0
= x

( )
( )
( )
( )
( )
( )

=

=
= =
= =
0
2 2
0
n
n
n
n
n
n
x q x q x
x P
x R
x
x p x xp
x P
x Q
x

This is convergent on R x <

( ) ( ) ( ) ( )
( ) ( ) 0 ... ' ... ' '
0 ' ' '
0 ' ' '
2
2 1 0
2
2 1 0
2
0 0
2
2 2
= + + + + + + + +
= |
¹
|

\
|
+ |
¹
|

\
|
+
= + +
∑ ∑

=

=
y x q x q q y x p x p p x y x
y x q y x p x y x
y x q x y x xp x y x
n
n
n
n
n
n

As near 0
0
= x , 0 → x , the equation behaves like
0 ' ' '
0 0
2
= + + y q y xp y x
This is an Euler form.
Indicial Equation: ( ) 0 1
0 0
= + + − q r p r r , Thus
2 1 2 1
| , r r r r r ≥ =
Therefore, ( )

=
+
= + + + =
0
2
2 1 0
...
n
n r
n
r
x a x a x a a x y for 0 , 0
0
> ≠ x a
From the indicial equation, there are three different forms of the general solution.

Form 1: { } { } Ζ ∉ −
2 1
r r

( )
( )
2 2 1 1
0
0 0 2
0
0 0 1
2
1
y c y c y
x x b x x y
x x a x x y
n
n
n
r
n
n
n
r
+ =
− − =
− − =

=

=

Form 2:
2 1
r r =
( )
2 2 1 1
1
1 1 2
1
1 1
1 ln
1
1
1
y c y c y
x r b x x y y
x r a x y
n
n
n
r
n
n
n
r
+ =
|
¹
|

\
|
+ + =
|
¹
|

\
|
+ =

=

=

Where the coefficients of the series are found by substituting into the differential
equation.

Form 3: { } { } Ζ ∈ −
2 1
r r
( )
2 2 1 1
1
2 1 2
1
1 1
1 ln
1
2
1
y c y c y
x r b x x ay y
x r a x y
n
n
n
r
n
n
n
r
+ =
|
¹
|

\
|
+ + =
|
¹
|

\
|
+ =

=

=

Where the coefficients of the series are found by substituting into the differential
equation.

Case 3: About an Irregular Singular Point
Where ( ) 0
0
= x P , ( )
( )
( )
|
|
¹
|

\
|

x P
x Q
x x
x x
0
0
lim does not exist or ( )
( )
( )
|
|
¹
|

\
|

x P
x R
x x
x x
2
0
0
lim does
not exist.

X.3 LINEAR 2
ND
ORDER PARTIAL DIFFERENTIAL EQUATIONS:

Where, ( ) ( ) y x g u f eu du cu bu au
y x yy xy xx
, = + + + + + and a,b,c,d,e & f are constants
or functions of x and y only.

Separation of Variables:
Step 1: Assume ( ) ( ) ( ) y Y x X y x u = ,
Therefore:

( ) ( )
( ) ( )
( ) ( )
( ) ( )
( ) ( ) y Y x X u
y Y x X u
y Y x X u
y Y x X u
y Y x X u
y
x
yy
xy
xx
'
'
' '
' '
' '
=
=
=
=
=

Step 2: Rearrange Equation into two ordinary differential equations

( ) ( )
( )
( )
¹
´
¦
= + Β
= + Α

− = Β = Α
0
0
λ
λ
λ
Y k
X
Y k X

Step 3: Considering the Homogeneous Boundary Conditions, when

( ) ( ) ( ) ( )
( ) ( ) ( ) ( )
( ) ( ) ( ) ( )
( ) ( ) ( ) ( ) 0 0 0 ,
0 0 0 0 0 0 ,
0 0 0 ,
0 0 0 0 0 , 0
= ⇒ = ⇒ =
= ⇒ = ⇒ =
= ⇒ = ⇒ =
= ⇒ = ⇒ =
L Y L Y x X L x u
Y Y x X x u
L X y Y L X y L u
X y Y X y u

As we are only interested in the non trivial solutions to the problem.
Step 4: Solving for the ODE with two boundary conditions
Case 1: 0 = λ
Solve as a regular ODE with 0 = λ .
If 0
2 1
= = c c , then 0 = λ is not an eigenvalue for the problem.
Case 2: 0
2
< − = µ λ
Solve as a regular ODE with
2
µ λ − = .
If 0
2 1
= = c c , then 0 < λ is not an eigenvalue for the problem.
Case 3: 0
2
> = µ λ
Solve as a regular ODE with
2
µ λ = .
If 0
2 1
= = c c , then 0 > λ is not an eigenvalue for the problem.
Step 5: For those values of λ where 0
1
≠ c or 0
2
≠ c , then find the periodic function that satisfies
the homogeneous boundary conditions.
Eg: If ( ) ( ) 0 sin
2
= = L c L X µ then
,... 3 , 2 , 1 , ,... 3 , 2 , 1 ,
2
2 2
= = ⇒ = = n
L
n
n
L
n
n
π
λ
π
µ
Therefore,
|
¹
|

\
|
=
L
x n
c X
n
π
sin
2

Step 6: Find the corresponding solution for the other ODE that was not solved in step 4. You only
need to consider the values of λ that were found in Step 4 and using the expression for µ (if
needed) from Step 5.
Step 7: Find the fundamental set of solutions from Steps 5 & 6.
( ) ( ) ( ) y Y x X y x u
n n n
= ,
By the superposition principle:
If
n
u u u ,..., ,
2 1
are solutions of a homogeneous linear PDE, then
( )
n n
u c u c u c y x u + + + = ... ,
2 2 1 1
is also a solution to the PDE.
Then ( ) ( ) ( ) ( ) y Y x X c y x u c y x u
n
n
n n
n
n n ∑ ∑

=

=
= =
1 1
, ,

Step 8: Under the non homogeneous boundary conditions, solve by using a method of the Fourier
series:
Eg: If ( )

=
|
¹
|

\
|

|
¹
|

\
|
=
1
sin ,
2
n
y
L
n
n
L
x n
e c y x u
π
πα
and ( ) ( ) x f x u = 0 ,
( )

=
|
¹
|

\
|
=
1
sin 0 ,
n
n
L
x n
c x u
π
where
n
c is the coefficient of the Fourier series (Fourier
Sine Series in this example) and is solved as such.
Step 9: Substitute the found constants back into the infinite series to express the final answer.
( ) ( ) ( ) ( ) y Y x X c y x u c y x u
n
n
n n
n
n n ∑ ∑

=

=
= =
1 1
, ,

X.3 ORDINARY DIFFERENTIAL EQUATIONS USING MATRICES:

Derivation of Methods:
x A x t x A t x
t x a t x a t x a t x
t x a t x a t x a t x
t x a t x a t x a t x
n nn n n
n
n n
n n
= ⇒ = ⇒
+ + + =
+ + + =
+ + + =
• •

) ( ) (
) ( ... ) ( ) ( ) (
...
) ( ... ) ( ) ( ) (
) ( ... ) ( ) ( ) (
2 2 1 1
2 2 22 1 21
2
1 2 12 1 11
1

where [ ]
n
n
ij
t x
t x
t x
x a A ℜ ∈
(
(
(
(
(
¸
(

¸

= =

) (
...
) (
) (
,
2
1

[ ]
c t t x
c
c
c
x x x x
x c x c x c x
n
n
n n
) ( ) (
...
| ... | |
...
2
1
2 1
2 2 1 1
Φ =
(
(
(
(
¸
(

¸

=
+ + + = ∴

Fundamental Matrix:
General Solution: c
e v e v e v
e v e v e v
e v e v e v
c t t x
t
nn
t
n
t
n
t
n
t t
t
n
t t
n
n
n
(
(
(
(
(
¸
(

¸

= Φ =
λ λ λ
λ λ λ
λ λ λ
...
... ... ... ...
...
...
) ( ) (
2 1
2 1
2 1
2 1
2 22 21
1 12 11

Particular Solution:
0 0
1
) ( x t c

Φ =

Homogeneous Solution:
General Solution:
c P Pe c e x
x A x
Jt At 1 −

= =
=

Particular Solution:
(
(
(
(
¸
(

¸

=
) 0 (
...
) 0 (
) 0 (
2
1
n
x
x
x
c

Inhomogeneous Solution:
General Solution:
( ) ( ) ( )
( ) ( ) ( ) ( ) ( )
( ) ( ) ( ) ( ) ( )

− Φ Φ + Φ =
Φ Φ + Φ =
+ =

dt t u t t c t t x
dt t u t t c t t x
t u t x A t x
1

Particular Solution:
(
(
(
(
¸
(

¸

=
) 0 (
...
) 0 (
) 0 (
2
1
n
x
x
x
c

n
th
Order linear, constant coefficient ODE:

( ) ( )
0 ' ' ' ...
0 1 2
1
1
= + + + + +

y a y a y a y a y
n
n
n

Let
( ) ( ) 1 2
1 3 2 1
, ,..., ' ' , ' ,
− −

= = = = =
n
n
n
n
y x y x y x y x y x
Therefore,

( )
( )
n n
x x
x y y x
x y y x
x y x
=
= = =
= = =
= =

1
4 3
3 2
2 1
... ... ...
' ' ' ' ' '
' ' ' '
'

( )
( )
( )
n n n n
n n
n
x a x a x a x a y y x
1 1 2 2 1 1 0
1
... '
− − −
− •
− − − − − = = =

Ax x =

(
(
(
(
(
(
(
(
(
¸
(

¸

− − − − − −
=
− − 1 2 3 2 1 0
...
1 0 ... 0 0 0 0
0 1 ... 0 0 0 0
... ... ... ... ... ... ...
0 0 ... 1 0 0 0
0 0 ... 0 1 0 0
0 0 ... 0 0 1 0
n n
a a a a a a
A
( )
(
(
(
(
(
(
(
(
(
¸
(

¸

− − − − − − −

= −
− −
λ
λ
λ
λ
λ
λ
1 2 3 2 1 0
...
1 ... 0 0 0 0
0 1 ... 0 0 0 0
... ... ... ... ... ... ...
0 0 ... 1 0 0
0 0 ... 0 1 0
0 0 ... 0 0 1
det
n n
a a a a a a
I A
By taking cofactors,
( ) ( )
( ) 0 ...
0 ... 1
0 1
2
2
1
1
0 1
2
2
1
1
= + + + + +
= + + + + + − =

a a a a
a a a a
n
n
n
n
n
n n
λ λ λ λ
λ λ λ λ

This is the characteristic equation of the original ODE